PENGARUH CAR, BOPO, NIM, NPL, DAN LDR TERHADAP ROA: STUDI KASUS PADA 10 BANK TERBAIK DI INDONESIA PERIODE 2007-2011 - Maria, Anne (University of Surabaya, 2015)
This study aimed to identify the influence of Capital Adequacy Ratio, Operating Expenses to Operating Income, Net Interest Margin, Loan Deposit Ratio to Return On Asset on the top 10 banks 2013 in Indonesia. This study used a quantitative approach and pooling data methods. The top 10 banks are PT Bank Mandiri (Persero),Tbk, PT Bank Rakyat Indonesia (Persero), Tbk, PT Bank Central Asia,Tbk, PT Bank Negara Indonesia (Persero),Tbk, PT Bank CIMB Niaga, Tbk, PT Bank Danamon Indonesia, Tbk, PT Pan Indonesia Bank, Tbk, PT Bank Permata, Tbk, PT Bank Internasional Indonesia, Tbk, and PT Bank Tabungan Negara (Persero) in the period 2007-2011. The result of this research indicate that Operating Expenses to Operating Income had negative and significant effect on Return On Asset. Net Interest Margin had positive and significant effect on Return On Asset. Capital Adequacy Ratio and Loan Deposit Ratio had positive and no significant effect to ROA. Non Performing Loan had negative and no significant effect on Return On Asset.